2018
DOI: 10.1016/j.stueduc.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a modified version of the Experiences of Teaching and Learning Questionnaire

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…After analyzing the effect of 105 variables on academic achievement, they found that the variable of teacher “availability and help” occupied the eleventh position, and “being friendly and respectful” with students occupied position 30. However, the present study shows that specific regulatory practices of teachers would have a positive impact on academic behavioral confidence, on reducing procrastination and on increasing students’ academic achievement, and can guide educational practice ( Vermunt, 1989 ; Willcoxson et al, 2011 ; Villasana et al, 2016 ; Utriainen et al, 2018 ).…”
Section: Resultsmentioning
confidence: 68%
“…After analyzing the effect of 105 variables on academic achievement, they found that the variable of teacher “availability and help” occupied the eleventh position, and “being friendly and respectful” with students occupied position 30. However, the present study shows that specific regulatory practices of teachers would have a positive impact on academic behavioral confidence, on reducing procrastination and on increasing students’ academic achievement, and can guide educational practice ( Vermunt, 1989 ; Willcoxson et al, 2011 ; Villasana et al, 2016 ; Utriainen et al, 2018 ).…”
Section: Resultsmentioning
confidence: 68%
“…Traditionally, the internal structure of a questionnaire is evaluated via Confirmatory Factor Analysis [2; 21; 29-31], 'which MODERNIZATION OF EDUCATION tests the theoretically justified measurement model against the data collected with the questionnaire' [32].…”
Section: Questionnairs Usedmentioning
confidence: 99%
“…Such information can be used to develop efficient programs and improve learning methods [ 12 ]. Diverse tools are available to examine the feedback and experiences of students with a learning environment and teaching – learning process in particular [ 1 , 13 , 14 ]. One of these tools is Entwistle et al’s (2003) experience of teaching–learning questionnaire (ETLQ), which was first developed in English [ 12 ].…”
Section: Introductionmentioning
confidence: 99%